Posted Offer Markets in Near-Continuous Time: An Experimental Investigation. - Davis, Douglas D.; Korenok, Oleg (Economic Inquiry, 2009)
This paper reports an experiment conducted to evaluate a “near-continuous” variant of the posted offer trading institution, where the number of periods in a market session is increased by reducing sharply each period's maximum length. Experimental results suggest that although decisions in time-truncated periods are not equivalent to periods of longer duration, extensive repetition improves considerably the drawing power of equilibrium predictions in some challenging environments. Nevertheless, significant deviations remain in the near-continuous framework. We also observe that the extra data collected in the near-continuous framework allow new insights into price convergence and signaling. (JEL C92, L12, L11) Reprinted by permission of the publisher.